Antropologi Sastra Dalam Novel Segala yang Diisap Langit Karya Pinto Anugrah - Nuriah, Mirza; Puspita, Yenny; Wahidy, Achmad (Indonesian Research Journal on Education, 2022)
The purpose of this study was to identify and describe the anthropology of literature in the novel Everything Diisap Langit by Pinto Anugrah. The research method used is descriptive qualitative method. Data collection techniques using documentation techniques. The results showed that the novel Everything Diisap Langit by Pinto Anugrah contained six elements of Minangkabau culture. The equipment for the life of the Minangkabau community includes production equipment, containers, food, clothing, shelter and means of transportation. In the livelihoods of the Minangkabau people, they work as workers or laborers, do business, grow crops and migrate to meet their daily needs. In Minangkabau society there are customs and rules that must be obeyed such as kinship, marriage and mutual cooperation. Minangkabau language is used as a tool to communicate. Minangkabau people have knowledge about the types of flora and natural phenomena. The Minangkabau community's religious system includes religion and mystical beliefs.